Penafsiran Ahsan Taqwim Dalam Qs. At Tin Ayat 4 (Studi Komparatif antara Tafsir Al Mishbah dan Tafsir Al Maraghi) - Muhammad Rizal; Ahmad Deski; Febri Wardani; Daniel Alfaruqi (JURNAL ILMIAH RESEARCH STUDENT, 2026)
This study was motivated by data from Kompas.com, which states that Indonesia ranks fifth in the world for the highest number of premature births, with 15 million cases globally per year and 1.1 million deaths due to complications. This prompted the author to examine the interpretation of “ahsan taqwim” (the best of creations) in QS. At-Tin/95:4 according to Tafsir Al -Misbah by M. Quraish Shihab and Tafsir Al-Maraghi by Ahmad Mustafa Al-Maraghi, along with a comparative analysis; the aim is to reveal the interpretations of both. Using a library research approach with the muqaran tafsir method, the primary sources are the Qur'an and the two tafsir, while the secondary sources include related journals, books, and theses. The results show that Shihab views ahsan taqwim as physically and psychologically perfect humans for worship and as caliphs of the earth, while Al-Maraghi views them as superior creations with reason for knowledge, power over creatures, and worldly pleasures. The author's analysis highlights the similarity in the superiority of humans but the difference in emphasis on spiritual versus intellectual-material functions.